2021
DOI: 10.1111/joss.12641
|View full text |Cite
|
Sign up to set email alerts
|

Sensory characterization of conventional and organic extra virgin olive oil by Check‐all‐that‐apply and emotional responses methods

Abstract: This study aimed to investigate the sensory characterization of commercial and organic extra virgin olive oils by the Check‐all‐that‐apply (CATA) and emotional responses methodologies. The samples were evaluated for viscosity and yellow color by 120 consumers using CATA, acceptance test, purchase intention test, emotional responses, and ideal scaling, allowing the construction of two External Preference Maps aimed to associate the results from the overall impression with the terms from CATA and the emotional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…In the current study, both descriptors were found to be negative drivers of liking for EVOO, despite being considered positive attributes by the official panel test method [ 19 ]. However, the fact that bitter taste was a negative driver of liking in EVOO among consumers fully confirmed several previous studies demonstrating that this sensation is generally disliked in oils [ 25 , 26 , 27 ]. A recent review concluded that the sensory perception of the consumers regarding a high-quality olive oil, typically being characterized by both bitterness and pungency at different intensities, matches to the perception of panel tasters in countries with a tradition of virgin olive oils consumption, but this correlation was not observed with consumers in non-traditional olive-oil-consuming countries [ 46 ].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In the current study, both descriptors were found to be negative drivers of liking for EVOO, despite being considered positive attributes by the official panel test method [ 19 ]. However, the fact that bitter taste was a negative driver of liking in EVOO among consumers fully confirmed several previous studies demonstrating that this sensation is generally disliked in oils [ 25 , 26 , 27 ]. A recent review concluded that the sensory perception of the consumers regarding a high-quality olive oil, typically being characterized by both bitterness and pungency at different intensities, matches to the perception of panel tasters in countries with a tradition of virgin olive oils consumption, but this correlation was not observed with consumers in non-traditional olive-oil-consuming countries [ 46 ].…”
Section: Discussionsupporting
confidence: 84%
“…The CATA test has been previously applied to link consumers’ emotions to the sensory characterization of a wide range of different food products (salted snacks, potato chips, yoghurt, cheese, snack bars and fruit, nuts, chocolate, fruit, and processed tomato products) [ 49 , 50 ]. Regarding oils, CATA was recently applied to investigate the sensory characterization of commercial and organic extra virgin olive oils [ 26 ] and to evaluate the acceptability and sensory characteristics of five sesame oil samples prepared with different technological processes [ 51 ]. To the best or our knowledge, the current study is the first to apply the CATA test to evaluate consumers’ perception of the sensory properties of food products over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emotion is one of the critical factors that consumers consider when making product purchase decisions (de Melo et al, 2021;Nasermoadeli et al, 2012). Positivity in emotions can add value to a product, whereas negativity can subtract value.…”
Section: Introductionmentioning
confidence: 99%